Juvenile recruitment, growth and maturation of Lipophrys pholis (Pisces: Blenniidae), from the west coast of Portugal - Faria, Cláudia Barreiros Macedo de (1996)
Data on the juvenile recruitment, growth and size at maturation of Lipophrys pholis in Portuguese waters are compared with the information available on the biology of this species at higher latitudes. In Portugal, recruitment extends for a much longer period, young fish grow faster and sexual maturation is earlier than at higher latitudes. There is a delay of 2–3 months between the appearance of the first eggs on the shore and the recruitment of the first juveniles to the pools.